(untitled) (Tzintzun, Revista de Estudios Históricos, 2016)
This article reviews the historiography from 1980 on the peasant participation in the armed movements in the rural areas of the New Spain between 1810 and 1821. It also tries to explain the origins of the new interest in the subject that arose in the decade of the 1980 and because the English-speaker historians were more interested in the subject than their Mexican colleagues. It pays attention in the importance of the social history of the colony, the international influence of debates on the peasants movements which originated themselves in the North American adventure in Vietnam, and the English-speaker fascination with the so call new cultural history. It reviews a series of contributions done by historians of several countries on the peasants’ attitude during the Mexican insurgency, including works of Tutino, Hamnett, Van Young, Guardino, Escobar Ohmstede, Ortiz Escamilla, Ducey, Guedea and Landavazo. It also describes some advances in compatible areas like new works on the insurgent leadership and the insurgent speech. It finishes with some opinions on the possibilities of advancing our knowledge of the reasons for the participation farmer in the war of independence.